english - Isti Naroh; Suratno (Jurnal Pendidikan dan Pengajaran, 2024)
Conventional learning causes boredom and a lack of student motivation in the learning process, resultingds in a decline in learning achievement in Natural and Social Sciences (IPAS). This research aims to develop Quartet Cards Based on Banyumas' Local Wisdom in science and science learning for fourth-grade elementary school, especially on the Unique Habits of the People Around Me. This type of research is research and development (R&D) using the ADDIE model. The subjects of this research were one learning media expert and one learning materials expert. The test subjects were 15 grade IV elementary school students. Data collection methods are observation, interviews, questionnaires, and tests. Data collection instruments are questionnaire sheets and test questions. This research uses quantitative descriptive analysis techniques, qualitative descriptive analysis, and inferential statistics. The research results were the assessment results from media experts 92%, materials experts 90%, small group trials 94.6%, large group trials 96.6%, and teacher responses 100%, so overall, the assessment was placed in the appropriate category. The results of the T-test show a significant difference in student learning achievement before and after the application of quartet card media in the learning process. The results of the N-gain test show that the Quartet Card media based on Banyumas Local Wisdom has moderate effectiveness in improving science learning outcomes. It was concluded that the Quartet Card media based on local wisdom in Banyumas Regency that was developed was very suitable for continuing science learning. The research implication is that the media developed can help students learn IPAS.